Analisis Determinan Penggunaan Informasi Akuntansi pada UMKM Kabupaten Deli Serdang - Ndruru, Elvin Susanti; Fauzi, Indra (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
The purpose of this study was to analyze and determine the influence of the determinants of the use of accounting information on SMEs in Deli Serdang Regency. This research is a quantitative research with a causal associative approach. The research studied is the scale of the business, the age of the company, accounting training and the use of accounting information. The population in this study are MSME businesses in the culinary field that are registered at the small and medium business cooperative office in the district. Deli Serdang in Kec. Tanjung Morawa and STM Hilir with a total population of 255 MSMEs. The sampling technique used non-probability sampling with purposive sampling of 68 samples. Data were analyzed using multiple regression analysis. The results of this study indicate that business scale, business age and accounting training have a positive and significant effect on the use of accounting information. Simultaneous test results show that business scale, business age and accounting training simultaneously affect the use of accounting information.